Optimising Connectivity and Energy : The Future of LoRaWAN Routing Protocols for Mobile IoT Applications - IZZAH NILAMSYUKRIYAH, BUANG; Kartinah, Zen; Syahrul Nizam, Junaini (ARQII Publication, 2025)
Abstract: The proliferation of Internet of Things (IoT) applications has significantly increased the demand for communication protocols that are both resilient and energy-efficient. Among these, Low Power Wide Area Network (LPWAN) technologies - specifically Long-Range Wide Area Network (LoRaWAN) - offer long-distance wireless connectivity for IoT devices, characterized by their extended transmission range and minimal energy consumption. However, the mobility of IoT devices introduces challenges in optimizing energy efficiency. This study provides a comprehensive review of energy-efficient routing algorithms for LoRaWAN in mobile IoT applications. A systematic approach is employed, adhering to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, to identify, evaluate, and synthesize pertinent literature, offering an in-depth exploration of existing methodologies, their advantages and limitations, and potential avenues for future research. Key topics examined include AI-enhanced adaptive data rate (ADR) methods, coding schemes based on the Chinese Remainder Theorem (CRT), and processes utilizing Variable Order Hidden Markov Models (VHMM). These approaches have demonstrated improvements in packet delivery ratios (PDRs), latency reduction, and energy efficiency within mobile IoT contexts. Despite notable advancements, significant opportunities remain for enhancing scalability, developing hybrid solutions, applying these methodologies in real-world contexts, and implementing robust security protocols. This paper contributes valuable insights into the current landscape of energy-aware routing protocols for LoRaWAN in mobile IoT applications and outlines critical areas for future research aimed at achieving sustainable and efficient IoT networks.